THE EFFECT OF CURRENT RATIO AND RETURN ON ASSETS ON THE STOCK PRICE OF PT DUTA PERTIWI TBK FOR THE 2013–2023 PERIOD - Agus Supriatna; N Rusnaeni; Tri Wartono (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the influence of the Current Ratio (CR) and Return on Assets (ROA) on the stock price of PT Duta Pertiwi Tbk during the 2013–2023 period. The method used is a descriptive quantitative approach with secondary data obtained from the company’s financial reports. The independent variables include CR, which reflects the company’s ability to meet short-term obligations, and ROA, which indicates the efficiency of asset utilization in generating profits. The dependent variable is the stock price, measured based on the closing price in the capital market. The analysis results show that partially, CR has a significant influence on stock prices, with a positive coefficient. This indicates that an increase in the company’s liquidity can boost investor confidence, thereby driving up stock prices. Conversely, ROA does not significantly affect stock prices. Simultaneously, CR and ROA explain 43.9% of the variability in stock prices, while the remainder is influenced by other factors outside the research model. This study highlights the importance of CR as a key indicator in determining stock prices, although other variables, such as macroeconomic factors or corporate strategies, also play a significant role. These findings provide insights for investors and corporate management in managing financial performance to enhance stock value in the capital market.